2012
DOI: 10.1210/me.2012-1140
|View full text |Cite
|
Sign up to set email alerts
|

ERα Phosphorylation at Y537 by Src Triggers E6-AP-ERα Binding, ERα Ubiquitylation, Promoter Occupancy, and Target Gene Expression

Abstract: Many transcription factors undergo transcription-coupled proteolysis. Although ligand binding activates ubiquitin proteolysis of estrogen receptor α (ERα), mechanisms governing this and its relationship to transcriptional activation were unclear. Data presented link cross talk between the Src kinase and liganded ERα with ERα activation and its ubiquitylation. Liganded ERα rapidly activates and recruits Src, which phosphorylates ERα at tyrosine 537 (Y537). This enhances ERα binding to the ubiquitin ligase/ERα c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 61 publications
3
66
0
2
Order By: Relevance
“…TSEC significantly reduced CE-mediated enhancement of ERa activity in endometrial and breast cancer cells by degrading ERa protein, in contrast with the E2-induced interaction of ERa with E6-AP for the ERa activation (Sun et al, 2012). However, TSEC caused a differential interaction of ERa with FBXO45 for the suppression of ERa activity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…TSEC significantly reduced CE-mediated enhancement of ERa activity in endometrial and breast cancer cells by degrading ERa protein, in contrast with the E2-induced interaction of ERa with E6-AP for the ERa activation (Sun et al, 2012). However, TSEC caused a differential interaction of ERa with FBXO45 for the suppression of ERa activity.…”
Section: Discussionmentioning
confidence: 84%
“…However, each hormone-induced ERa degradation was accompanied by an opposite effect on ERa activity: TSEC-induced ERa degradation was associated with inhibition of ERa activity, whereas CE-mediated ERa destabilization was correlated with enhancement of ERa activity. Previous studies also revealed that enhanced estradiol-induced ERa activation is associated with ERa degradation (Wijayaratne and McDonnell, 2001;Callige and Richard-Foy, 2006), and a specific E3 ubiquitin ligase, such as E6-AP, might be involved in this process (Li et al, 2006;Sun et al, 2012). However, the molecular mechanism underlying the functional correlation between estrogen-induced ERa degradation and ERa activation has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For ER/ Y537 dephosphorylation in cells, MCF-7 cells were cultured for 24 hours in medium without serum and phenol red, which were then pulsed with estrogen (100 nmol/L for 30 minutes), and lysates were then subjected to immunoprecipitation with p-ER/Y537 antibody. Precipitates were subjected to Western blot analysis with ER or p-Tyr antibody (14).…”
Section: Er/y537 Dephosphorylation In Vitro and In Cellsmentioning
confidence: 99%
“…Recent studies further showed that Src-induced ER/Y537 phosphorylation is essential for ER nuclear export (13) and for E6AP-triggered ER degradation (14). Furthermore, increased levels of p-ER/ Y537 expression in clinical breast cancer are associated with a poor therapeutic response to TAM (15) and the Tyr537Asn mutation was detected in metastatic breast cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LYN, as measured by immunohistochemistry (IHC), is associated with an epithelial-to-mesenchymal transition and correlates with a shorter overall survival in breast cancer (3). SRC engages in bidirectional crosstalk with the estrogen receptor α (ERα) (4), in which its kinase phosphorylates ERα at Y537 (5), resulting in an enhancement of ER transcriptional activity (6).…”
Section: Introductionmentioning
confidence: 99%